Ordinance No. 30: Concealed Weapons, in RED LODGE PICKET, Sep. 12, 1893, at 3, § 2 - (:unkn) unknown (My University, 1893)
Any person who shall within the limits of this town discharge, or fire, or cause to be discharged or fired any pistol, revolver, gun, rifle or any other firearm shall be deemed guilty of a misdemeanor and upon conviction be fined not less than five dollars ($5.00) nor more than one hundred dollars ($100.00) or be imprisoned in the town jail not more than thirty days or both in the discretion of the Court.
Keywords: DISCHARGE